Management Alternatives to Refractory Hypoxemia in COVID-19 Patients: Review of the Literature (Revista de Medicina Clinica, 2022)
Introduction: COVID-19 pandemic has created a challenge never seen in health systems, generating a burden that has been growing exponentially. Objective: The aim of this review is to know the indications for such therapy since the two main causes of death in this pathological process are unresponsive hypoxemia associated with respiratory distress and shock with its subsequent multi-organ failure. Methods: A recent literature review was conducted on extracorporeal membrane support, which has been used in patients with ventilatory failure who do not respond to prone management and with adequate parameters. Results: There is very little scientific evidence available to date given the limitations derived from the pandemic time as well as the technological resource to be reviewed in this publication given that there are very few expert groups in the area, however it was found in the review that there is a formal indication of such support in COVID-19 who do not respond to traditional management measures. Conclusion: The support with extracorporeal membrane has emerged as an alternative to consider in the ranking of therapeutic measures in patients who do not respond to traditional management, these patients must be very rigorously selected, and a search should be made to prolong survival.
Keywords: Oxygenation; Risk; Support; Ventilation